Comparison of dynamic and static strategy for hedge ratio determination - Lím, Drahoslav; Rada, Miroslav; Frýd, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis compares the effectiveness of static and dynamic strategies for determining the hedge ratio in commodity markets. I focus on two business scenarios: an airline company purchasing jet fuel hedged with WTI crude oil futures and a shipping company purchasing gasoline hedged with RBOB gasoline futures. My objective is to lower the volatility of changes in weekly costs in USD per gallon for the given commodity. Using OLS regression on time series data from 2021--2024, I estimate optimal hedge ratios that minimize variance for both strategies. Empirical results show that both hedging strategies successfully reduced the volatility of changes of weekly costs per gallon for a given commodity. The reductions were more substantial in the airline case, where the first differences of spot and futures prices showed strong positive correlation. In the shipping company case, the weaker positive correlation limited the potential of both strategies, but volatility was still modestly reduced. In both scenarios, the dynamic strategy slightly outperformed the static one, supporting the idea that responding to market changes can improve hedging performance. These results demonstrate that the effectiveness of hedge ratios depends not only on their construction method but also on the underlying correlation type of the market. While the OLS framework produced usable estimates, the presence of volatility clustering in all price series suggests that models explicitly accounting for heteroskedasticity---such as ARCH or GARCH---may offer a more robust alternative for future hedge ratio estimation.
Vedoucí práce: Miroslav Rada
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor bakal. práce]; bakalářské práce; bachelor's theses